Effect of processing parameters to the fish oil from fish waste via modified soxhlet extraction - Farhan, Mohd Said; Nurlisa Syahiera, Mohd Rapidi; Nurul Syakira, Mohamed Ibrahim; Nur Hidayah, Mat Yasin; Nur Fathin Shamirah, Daud (Akademi Sains Malaysia, 2022)
The oil production and fatty acid methyl ester (FAME) contents of fish waste were studied. Solvent, temperature, and extraction time were the processing parameters involved. The oil and FAME were extracted using a modified soxhlet extraction method. The best solvent for fish oil extraction was found to be ethanol, which yielded 49.0%, followed by ethanol:heptane (1:1), methanol:heptane (1:1), and methanol. The oil extract composition contained a high yield of oleic acid (C18:1), ranging from 42% to 66%. Followed by palmitic acid (C16:0), palmitoleic acid (C16:1), and stearic acid (C18:0). According to the statistical model obtained, at the 95% confidence level, extraction time had a significant effect on both oil and oleic acid yield (C18:1). These results demonstrated that a high oleic acid fraction can be obtained from fish waste with ethanol, implying that there is a high potential for cost-effective biofuel production.